2019
DOI: 10.5089/9781513521565.001
|View full text |Cite
|
Sign up to set email alerts
|

Money Creation in Fiat and Digital Currency Systems

Abstract: To support the understanding that banks’ debt issuance means money creation, while centralized nonbank financial institutions’ and decentralized bond market intermediary lending does not, the paper aims to convey two related points: First, the notion of money creation as a result of banks’ loan creation is compatible with the notion of liquid funding needs in a multi-bank system, in which liquid fund (reserve) transfers across banks happen naturally. Second, interest rate-based monetary policy has a bearing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Recent research (e.g. Gross and Siebenbrunner, 2019) has also shown that the monetary transmission mechanism to the real economy within a multibank financial system using central bank digital currencies (CBDCs) in a completely cashless economy would work analogously to the mechanism in the fiat money system (i.e. money without intrinsic value as opposed to commodity money) currently in place.…”
Section: Opportunities For Blockchain Use Due To the Pandemicmentioning
confidence: 99%
“…Recent research (e.g. Gross and Siebenbrunner, 2019) has also shown that the monetary transmission mechanism to the real economy within a multibank financial system using central bank digital currencies (CBDCs) in a completely cashless economy would work analogously to the mechanism in the fiat money system (i.e. money without intrinsic value as opposed to commodity money) currently in place.…”
Section: Opportunities For Blockchain Use Due To the Pandemicmentioning
confidence: 99%
“…These two events ignited a conversation about the technicalities of money creation that went beyond the elite circles of economic experts to which it had thus far been constrained. The insights that money was created by private banks following a profit-motive, that such private banks' monies were made homogeneous and legitimate by a State accepting them in payment of taxes, and that money was thus in practice created "out of thin air, " gradually extended among activists and scholars (Ryan-Collins et al, 2011;Benes and Kumhof, 2012;Werner, 2014;Kumhof and Jakab, 2016), and were eventually confirmed by key actors in the governance of today's monetary system such as the Bank of England (McLeay et al, 2014) or the IMF (Gross and Siebenbrunner, 2019). "The Great Monetary Settlement, " as Martin (2014) frames the alliance between profitseeking bankers and stability-seeking rulers first implemented through the creation of the Bank of England, set the stage for the growth of monetary society and the progress of capitalism (Ingham, 2008;Desan, 2014;Martin, 2014).…”
Section: Governing Moneymentioning
confidence: 99%
“…That is, access to credit (or new money) is granted to those that are already creditworthy. Bolstering economic swings because bankers grant credit when they are optimistic about the economy and constrain debt creation when less optimistic; a procyclical behavior that, among others, results in regular financial crisis and systemic instability (Benes and Kumhof, 2012;Gross and Siebenbrunner, 2019).…”
Section: Governing Moneymentioning
confidence: 99%
“…These issuances are studied through sectoral balance sheet dynamics based on double-entry bookkeeping principles. This approach is based on the following works: [4,[13][14][15].…”
Section: The Second Pillar: a Sectoral Balance Sheet Dynamics; The Crmentioning
confidence: 99%